2018
DOI: 10.1111/jasp.12530
|View full text |Cite
|
Sign up to set email alerts
|

Perceived acculturation preferences of minority groups and intergroup discrimination: When culture‐specific intergroup norms matter

Abstract: The present research seeks to show that culture-specific variables can moderate the impact of general determinants of intergroup discrimination, usually assumed to operate identically across cultures. The present paper reports the results of two studies testing the hypothesis that, in France, the cultural norm of new laïcité (a French-specific ideology of secularism) can moderate the impact of the perceived host culture adoption and national identification on discrimination against immigrants. We conducted a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 45 publications
2
16
0
2
Order By: Relevance
“…In other words, our results are compatible with the interpretation that adopting the host culture voluntarily led majority members to perceive the immigrant as being more identified with the host nation, which, in turn, led them to perceive him as deserving to be granted rights. These results are consistent with and extend previous research showing the influence of perceived acculturation practices on perceived host nation identification and the effect of this perceived identification on majority members' attitudes towards immigrants (Anier et al, 2018;Roblain et al, 2016). We observed that the direct effect ceased to be significant once the mediator was introduced in the model in Study 1, while it only decreased and remained significant in Study 2.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In other words, our results are compatible with the interpretation that adopting the host culture voluntarily led majority members to perceive the immigrant as being more identified with the host nation, which, in turn, led them to perceive him as deserving to be granted rights. These results are consistent with and extend previous research showing the influence of perceived acculturation practices on perceived host nation identification and the effect of this perceived identification on majority members' attitudes towards immigrants (Anier et al, 2018;Roblain et al, 2016). We observed that the direct effect ceased to be significant once the mediator was introduced in the model in Study 1, while it only decreased and remained significant in Study 2.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, these studies demonstrated that perceived host nation identification was a key predictor of majority members' attitudes toward immigrants: immigrants who adopted the host culture were perceived as more strongly identified with the host nation, which in turn led to more positive attitudes toward them. Anier et al (2018) replicated this mediating role of perceived identification with the host nation and extended this result by showing that it also applies to discriminatory behaviors. In line with this research, we predict a positive link between perceived identification and support for the legal recognition of immigrants.…”
Section: The Mediating Role Of Perceived Identification With the Hostmentioning
confidence: 56%
“…Previous experimental work has found causal effects of multiculturalism and colorblindness on stereotyping and prejudice (Wolsko, Park, Judd, & Wittenbrink, 2000). The present study certainly offers a sound basis for further development in this direction by testing the effects of interculturalism and secularism (for initial evidence, see Anier et al, 2018;Scott & Safdar, 2017). Ideally, these experiments should be conducted by controlling for national context effects, something that is still lacking in the literature (see Guimond et al, 2014).…”
Section: Limitations and Future Researchmentioning
confidence: 79%
“…More specifically, after 40 years of research focussing on personal attitudes toward multiculturalism and assimilation, there is now strong evidence showing the importance of distinguishing between the perceived cultural or group norms, that is the perceived level of support in a country for a given national integration policy, from personal attitudes, that is the extent to which individuals personally support these norms (see Guimond, de la Sablonnière, & Nugier, 2014;Guimond, Streith, & Roebroeck, 2015;Pelletier-Dumas, de la Sablonnière, & Guimond, 2017). Whereas national integration policies can have little direct impact on personal attitudes (Van de Vijver, Breugelmans, & Schalk-Soekar, 2008), they can have a strong impact on the perceived cultural norms, and it is through these norms that they can shape how the population feels, thinks, and behaves toward immigrants (Anier, Badea, Berthon, & Guimond, 2018;Guimond et al, 2013;Schlueter et al, 2013). However, it is unknown how the perceived cultural norms associated with national integration policies develop and why some norms have more of an impact than others.…”
Section: Introductionmentioning
confidence: 99%
“…Integration and multiculturalism are the two strategies of acculturation. In other words, two sides of a coin of acculturation: the former is used by the non-dominant cultural groups within the larger society to seek a relationship with the host society while maintaining their heritage culture and identity and the later one, on the other hand, is employed by the counterpart larger society that respects ethnocultural groups' cultural identity and diversity and provide them opportunities to interact with diverse dominant and non-dominant cultural groups in the larger society (Anier, Badea, Berthon, & Guimond, 2018;Merola, Coelen, & Hofman, 2019;Moore & Barker, 2012;Safdar, Chuong, Lewis, 2013).…”
Section: Introductionmentioning
confidence: 99%